Hidrólise enzimática de bagaço de malte usando tecnologias alternativas visando à obtenção de açúcares fermentescíveis - Luft, Luciana (2016)
This work aimed to study the enzymatic hydrolysis of malt bagasse, using mechanical agitation, ultrasonic probe and supercritical CO2. Enzymatic hydrolysis was performed on granular starch. For this, was used a commercial amylolytic complex suitable for this type of hydrolysis, STARGENTM 002. For each technology were studied different variables. The first planning was carried out for the hydrolysis assisted by mechanical agitation and the variables studied were temperature (°C), enzyme concentration (%, m/m) and substrate concentration in the medium (m/m). TRS concentrations were found up to 75.5 g per kg of substrate and all variables had a significant effect on the response. This concentration of TRS was defined as mass yield of the process and this yield was corroborated by a kinetic, developed under the same conditions, with slight increase in temperature (70°C). From this initial planning, the temperature variables (70°C), enzyme concentration (8.2%) and substrate concentration (170 g.L-1) were fixed to carry out the hydrolysis assisted by direct and indirect ultrasound. The variables were investigated in the second planning were amplitude (%) and pulse factor (-) for 2 hours of reaction. With the application of direct sonication, it was possible to achieve 100% efficiency in the starch conversion process. The TRS for the best essay (5) was 370.86 g.kg-1. For indirect sonication TRS concentration at the best condition (run 6) was 162.96 g / kg of substrate. A kinetic assay for the best condition under direct sonication was carried out for 3 hours, confirming that the ultrasound increases the reaction rate resulting in better yields in less time compared to the other techniques. For reactions with supercritical CO2 was studied the influence of the moisture content, temperature and pressure, where the best result among all the reactions was using at pressure 175 bar, 40 °C for temperature and moisture content of 80%, resulting in 104.28 g of TRS per kg of dry pulp. Ultrasound showed better results than other technologies investigated in this study.